Soil fertility and productivity in rice (Oryza sativa)-wheat (Triticum aestivum) cropping system as influenced by sunnhemp (Crotalaria juncea) green manuring - Mahapatra, B S; Kumar, Ajay; Misra, Alabhya; Kumar, Rajeev; Pareek, R P (The Indian Journal of Agricultural Sciences, 2005)
A field experiment was conducted during 2001-2002 and 2002-2003 on Mollisols of the university at Pantnagar, to study the effect of green manuring involving 4 genotytpes of sunnhemp (Crotularia juncea L.) on the biomass production, total productivity, nutrient removal in rice (Oryza sativa L.)-wheat (Triticum aestivum L. emend. Fiori & Paol.) system as well as changes in available nitrogen, total nitrogen, 6 N hydrolysable nitrogen and organic carbon content in soil. Among sunnhemp genotypes ’NDAUT (C) 2’ recorded highest number of root nodules (29.8 /plant), and their fresh weight (449 mg/plant). The fresh and dry biomass accumulation by ’NDUAT (C) 2’ genotype was highest compared with the other genotypes. Its incorporation as green manure gave higher grain yield in rice-wheat sequence (ie 3647 kg/ha of rice and 1569 kg/ha of wheat). Nitrogen uptake was higher owing to green manure application as compared to control, green manuring of ’NDUAT (C) 2’ recorded highest N uptake of grain + straw (66.82 kg/ha in rice and 31.95 kg/ha in wheat) among sunnhemp genotypes. The organic carbon content in soil due to green manure incorporation was increased at the end of two year cropping sequence. ’PAU (C) 1 ’ green manuring (0.730% organic carbon) resulted in 15.5% increase in organic carbon content over the control (0.632% organic carbon). Available N also increased in soil due to green manuring when compared to control. The 6N hydrolysable nitrogen was also higher in green manured plots compared with the control.